The Enforcement of Equal Opportunity Laws Under Imperfect Information: Affirmative Action and Alternatives - Lundberg, S. J. (Quarterly Journal of Economics, 1991)
Journal Article The Enforcement of Equal Opportunity Laws Under Imperfect Information: Affirmative Action and Alternatives Get access Shelly J. Lundberg Shelly J. Lundberg University of Washington Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 106, Issue 1, February 1991, Pages 309–326, https://doi.org/10.2307/2937919 Published: 01 February 1991